MPLEMENTASI REVOLUSI INDUSTRY 4.0 DALAM MENDUKUNG AKSELERASI INFORMASI KEBERBAKATAN OLAHRAGA MELALUI PEMBELAJARAN PENDIDKAN JASMANI - Ahmad, Nur; Kholis, Moh. Nur (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
The Progress of the World of Education with the 4.0 Industrial Revolution marked by the increasing era of digital manufacturing is driven by four factors: 1) an increase in data volume, computing power, and connectivity; 2) the emergence of analysis, capabilities, and business intelligence; 3) the occurrence of new forms of interaction between humans and machines; and 4) improvement of digital transfer instructions to the physical world, such as robotics and 3D printing. The World of Learning Education Particularly in sports is also highly developed along with the revolution of the era, namely Industrial Revolution 4.0. The emergence of this development is marked by the increasing number and sophistication of learning aids and sport science that can be connected with an exercise application or sports learning that can easily be accessed through the internet network. Physical Education in the School is a part of sports that is directly related to students, in this case, it is very appropriate and strategically ideal for finding talent or sports scenting, with such developments expected to be able to contribute significantly to the achievement of sports coaching. The minimum contribution is in the form of important information for sports practitioners related to sport height owned by students in Indonesia. Tallent sports information should be connected to an application that can be accessed by stakeholders or sports coaching practitioners so that in this case it can be directly followed up as a long-term coaching reference in determining the talent program. The emergence of advancing times that continue to grow or commonly referred to as the 4.0 industrial revolution today will provide the right opportunity for the acceleration of the progress of Indonesian sports.